Upaya Pengembangan Kreativitas Dalam Pembelajaran Matematika dengan Metode Pertanyaan Terbuka, Penemuan dan Diskusi - Wiharyanti Wiharyanti (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
This study aims to obtain an overview or description of how the process of learning mathematics with the method of open questions, discovery, and discussion can develop the creativity of students of class 1 semester 1 of SMA N 1 Kasihan Bantul. This research is a classroom action research consisting of two cycles. Each cycle is carried out with steps of planning, action, observation and reflection. Data to describe how the process of learning mathematics by the method of open questions, discovery, and discussion can develop student’s creativity obtained from field notes and observations. Data from the student creativity questionnaire to strengthen the description. Tests at the end of each cycle are used to support the results of the study. The actions taken in both cycles have been able to develop students' creativity. This is reinforced by the results of the analysis of the questionnaire. The average level of student creativity has increased, before the action, the average total score of students' creativity 36.068 is included in the category enough, after cycle I the average total score of student creativity is 48.205 included in the good category, and at the end of cycle II on average the total score of 52.97 students' creativity is included in the good category.